2010
DOI: 10.1007/s00280-010-1340-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacologic study of BNP7787, a novel chemoprotector in patients with advanced non-small cell lung cancer

Abstract: PurposeWe conducted a phase I trial of BNP7787 (disodium 2,2′-dithio-bis-ethane sulfonate, Tavocept™), a novel chemoprotective and antitumor enhancing agent administered in combination with paclitaxel and cisplatin. The primary aim was to determine a safe and potentially efficacious BNP7787 dose for preventing and mitigating paclitaxel- and cisplatin-induced toxicities and to evaluate for preliminary evidence of efficacy of treatment.Patients and methodsTwenty-two patients with stage IIIB/IV non-small cell lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A few components which can protect different tissues from toxic agents were clinically tested, showing conflicting results. No conclusive reports confirming their effectiveness have been provided [44, 45] and a reduction of anticancer activity was suspected [46]. Several neurotrophins were tested but there was no evidence of neuroprotection [4750].…”
Section: Introductionmentioning
confidence: 99%
“…A few components which can protect different tissues from toxic agents were clinically tested, showing conflicting results. No conclusive reports confirming their effectiveness have been provided [44, 45] and a reduction of anticancer activity was suspected [46]. Several neurotrophins were tested but there was no evidence of neuroprotection [4750].…”
Section: Introductionmentioning
confidence: 99%
“…Results, however, were conflicting, and the effectiveness of these agents is inconclusive. Indeed, the use of these agents may actually reduce anticancer activity (Masuda et al, 2011;Moore et al, 2003).…”
Section: Prevention Of Cipnmentioning
confidence: 99%
“…Studies conducted in human tumour xenografts demonstrated that the agent does not interfere with the efficacy of chemotherapy (Boven et al, 2002). Masuda et al (2011) conducted a phase I trial of BNP7787 (disodium 2,2'-dithio-bis-ethane sulfonate, Tavocept™) primarily to determine its safety and potential efficacy to prevent and mitigate paclitaxel-and cisplatininduced toxicities. Twenty-two patients with stage IIIB/IV non-small-cell lung cancer (NSCLC) received BNP7787 alone one week before co-administration of BNP7787 with paclitaxel followed by cisplatin.…”
Section: Tavocept (Disodium 22´-dithiobisethane Sulfonate Bnp7787 mentioning
confidence: 99%
“…Tavocept is converted to mesna in the kidneys, which then locally inactivates the toxic platinum species . In preclinical studies, Tavocept protected against cisplatin nephrotoxicity in both rats and dogs, and the use of Tavocept before cisplatin in people allows a 75% decrease in fluid diuresis . A similar decrease in fluid diuresis volume requirements would be ideal for dogs at risk of volume overload using the standard cisplatin administration protocol.…”
mentioning
confidence: 99%
“…25 In preclinical studies, Tavocept protected against cisplatin nephrotoxicity in both rats and dogs, and the use of Tavocept before cisplatin in people allows a 75% decrease in fluid diuresis. [26][27][28] A similar decrease in fluid diuresis volume requirements would be ideal for dogs at risk of volume overload using the standard cisplatin administration protocol. Tavocept does not contain the free thiol group that could diminish the antitumor effects of cisplatin.…”
mentioning
confidence: 99%